Volume-Returns Nexus in Emerging Gulf Markets - Ahlem NAJAH (Academic Finance)
Purpose: The aim of this study is to examine the relationship between trading volume and stock returns in the Saudi Stock Exchange (Tadawul) and Dubai Financial Market (DFM) for 2018-2024.